Morality, Technology, and Law: An Analysis of Online Gambling Law Enforcement - Farhana Farhana; Mimin Mintarsih; Rana Fitri; Khitta El Manzyla (AMCA, 2026)
The phenomenon of online gambling reflects a clash between morality, digital technology, and law, which has not yet fully adapted. Morally, gambling practices are rejected from the perspective of religion and Pancasila, yet the digital reality makes gambling increasingly accessible, cross-border, and difficult to control. From a global perspective, various countries have developed three legal approaches to regulating online gambling: the prohibitive model, the legal-restrictive model, and the legal-liberal model. Indonesia still adheres to the prohibitive model based on the Criminal Code (KUHP) and the Electronic Information and Transactions Law (ITE Law), but faces serious challenges in implementation due to its transnational and technological nature. The analysis shows the need for a hybrid approach that combines prohibition rooted in moral norms with adaptive regulation that leverages technology, international cooperation, and public protection. Within a responsive legal framework, law enforcement against online gambling should not only emphasize repressive measures but also educational, collaborative, and preventive aspects, making it more effective in addressing the dynamics of the digital era.